La dimension historique dans le vécu d’une figure mythique : Catherine II - Maaouche, Imen (Journal of Human Sciences, 2018)
This article on a work by Andrei Makine, A beloved lady, aims to study the parameters of a rehabilitation project of a mythical figure Catherine II of Russia, and that through the study of subversive writing and an art of corroboration of supreme realities appropriate to the experience of this tsarine. Realities, on which history has taken the step.